96.9k views
5 votes
Identify a possible first step using the elimination method to solve the system and then find the solution to the system.

3x-5y=-2
2x+y=3

User Kevin Dong
by
4.6k points

1 Answer

6 votes

Answer:x = 1

y = 1

Explanation:

The given system of simultaneous equations is expressed as

3x - 5y = - 2 - - - - - - - - - - - - 1

2x + y = 3 - - - - - - - - - - - - - 2

The first step is to decide on which variable to eliminate. Let us eliminate x. Then we would multiply both rows by numbers which would make the coefficients of x to be equal in both rows.

Multiplying equation 1 by 2 and equation 2 by 3, it becomes

6x - 10y = - 4

6x + 3y = 9

Subtracting, it becomes

- 13y = - 13

y = - 13/- 13 = 1

The next step is to substitute y = 1 into any of the equations to determine x.

Substituting y = 1 into equation 2, it becomes

2x + 1 = 3

2x = 3 - 1 = 2

x = 2/2 = 1

User Cos Callis
by
4.9k points